Unveiling forest vertical structure across China through stratified effective plant area index using extensive UAV LiDAR and multi-source remote sensing data - Zhiyong Qi; Zitong Bai; Haitao Yang; Yao Wang; Kai Cheng; Zekun Yang; Ang Chen; Tianyu Xiang; Yu Ren; Yixuan Zhang; Yuling Chen; Qingpeng Wang; et al. (Remote Sensing of Environment, 2026)

Effects of aquatic vegetation on sediment microbial communities and potential nitrogen cycling functions in a shallow lake - Sile Wen; Wangting Yang; Lan Zhou; Yuling Yang; Jinghao Jin; Bingjie Ren; Yuzhi Song; Yanan Bai; Lidong Shen (Journal of Soils and Sediments, 2026)

Vibration transmission characteristics of Camellia oleifera tree under excitation - Qingsong Li; Daochun Xu; Yuling Zhang; Xiaopeng Bai; Wenbin Li; Yuan He; Yuewei Ma (Computers and Electronics in Agriculture, 2026)

Polystyrene microplastics disrupt the blood-testis barrier via CEBPB-driven lysosomal autophagy and induce ferroptosis-like injury in human sperm, compromising embryo development - Man Wu; Lei Li; Tianxin Zhao; Yuling Mao; Jiajing Lin; Xiaomin Li; Yanling Bai; Feixue Han; Shuyan Chen; Tianwen Peng; Chen Liao; Xin Ye; et al. (Journal of Hazardous Materials, 2026)

Characteristics of soil organic carbon and its stability under different vegetation types and restoration years in Hongze lake wetland, China - Yanan Bai; Haikun Wu; Huifeng Lu; Yuling Yang; Yanping Wang; Lei Dai; Yuchun Ma; Jinqi Wang; Yuzhi Song; Lidong Shen (Journal of Environmental Management, 2026)

Shoot apical meristem-dependent adventitious bud induction from embryo axes of castor bean (Ricinus communis L.) via optimized cytokinin-auxin ratio - Liang Bai; Liying Shan; Jian Song; Mengchen Xu; Yue Wang; Ruiyan Guo; Yanli Jin; Yangguang Duan; Yuling Zhang; Zhimin Jiang; Jilong Zhong; Yan Cheng (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

A review of aluminum-based hydrotalcite for persulfate activation: Tuning reactive species for efficient organic pollutant degradation - Binwei Lian; Yuling Tian; Rusheng Bai; Linfeng Chen; Yayang Tian (Journal of Environmental Sciences, 2026)

The plant ontology of cell types - Hongyu Chen; Pu Liang; Xiaolin Lu; Shuai Jiang; Jingjing Jin; Jiaqi Cai; Yaqian Lu; Dihuai Zheng; Jie Yao; Qinjie Chu; Huixia Shou; Chengxin Fu; et al. (Molecular Plant, 2026)

Utilizing phosphogypsum-derived CaAl LDH-chitosan to remove Pb2+ from oil/gas field wastewater: Adsorption behavior and competitive mechanism - Jing Bai; Qijia You; Yushuan Peng; Zhihao Li; Yuling Zhang; Qiulin Deng; Huiwei Liao; Faqin Dong; Xiaofeng Zeng; Zixun Yan (Process Safety and Environmental Protection, 2025)

Trophic status impacts the potential significance of anaerobic methane oxidation driven by multiple electron acceptors in Lake Taihu sediments - Wangting Yang; Qinan Hu; Hechen Huang; Jinghao Jin; Bingjie Ren; Sile Wen; Yuling Yang; Yefan He; Yanping Wang; Yanan Bai; Yuzhi Song; Lidong Shen (CATENA, 2025)

Cascade nanozyme of multi-antioxidant Mn-doped carbon dots counters cytokine storm in acute lung injury - Pengli Gao; Hongchengcheng Chen; Yuling Bai; Jiaqian Li; Xiaoli Wang; Jingying Jiang (Chemical Engineering Journal, 2025)

The rhizosphere as a hotspot for nitrite- and nitrate-dependent anaerobic oxidation of methane in paddy fields - Yanping Wang; Yanan Bai; Lidong Shen; Bo Shang; Yang Ji; Xupeng Miao; Bingjie Ren; Yuling Yang; Wangting Yang; Zhaozhong Feng (Environmental Pollution, 2025)

Fe/Mo synergistic confinement in controlled N-doped carbon nanotubes frameworks: Multiscale insights and octogen degradation in multisolvent systems–performance, interfacial mechanisms, and electronic optimization - Junlan Tang; Jinmao Ma; Panpan Zhou; Jihui Zhang; Xiaojun Wang; Yuqian Shi; Jiaming Xu; Xiangru Zhou; Yuling Bai; Jiade Lin; Chi Chen; Lincheng Zhou; et al. (Chemical Engineering Journal, 2025)

Tm-1 back in business: an allele from Solanum pennellii accessions plays a major role in ToBRFV resistance - Romanos Zois; Mireille van Damme; Martin Verbeek; Luuk D. H. Veenendaal; Yuling Bai; Anne-Marie A. Wolters (Theoretical and Applied Genetics, 2025)
Key message The Tm-1 allele from Solanum pennellii accessions together with an additional, likely recessive, locus are required for complete ToBRFV resistance. Abstract The Tobamovirus Tomato Brown Rugose Fruit Virus (ToBRFV) poses a significant threat to global tomato production. ToBRFV is a mechanically transmitted virus containing a single-stranded positive sense RNA genome. Disease symptoms include brown, rough patches on fruit surfaces, leaf mosaicism and shape abnormalities, and, in advanced stages, total collapse of infected plants. ToBRFV was first detected in the Middle East in 2014 and has rapidly spread to multiple countries across Asia, Europe, and America. In recent years, numerous studies have focused on the identification of ToBRFV resistance traits that are suitable for tomato breeding programs. In this study, we identified five ToBRFV-resistant accessions of Solanum pennellii , a wild relative of cultivated tomato. We confirmed that the major gene controlling this resistance trait is the S. pennellii allele of Tm-1 . Tm-1 was previously identified in S. habrochaites as a semidominant Tomato Mosaic Virus (ToMV) resistance gene. Our results show that full resistance to ToBRFV disease requires an additional undescribed locus. These results show the potential of S. pennellii as a novel source of resistance against ToBRFV.

Advances in digital camera-based phenotyping of Botrytis disease development - Laura Groenenberg; Marie Duhamel; Yuling Bai; Mark G.M. Aarts; Gerrit Polder; Theo A.J. van der Lee (Trends in Plant Science, 2025)

Impact of conversion of coastal wetlands into paddy fields on the process of nitrite-dependent anaerobic methane oxidation - Qinan Hu; Weiqi Wang; Wangting Yang; Yuling Yang; Yanan Bai; Yefan He; Bingjie Ren; Yanping Wang; Jinghao Jin; Lidong Shen (Soil Ecology Letters, 2025)

Comparative transcriptomics of susceptible and resistant Cucumis metuliferus upon Meloidogyne incognita infection - Xiaoxiao Xie; Junru Lu; Runmao Lin; Jian Ling; Zhenchuan Mao; Jianlong Zhao; Qihong Yang; Shijie Zheng; Yan Li; Richard G. F. Visser; Yuling Bai; Bingyan Xie (Planta, 2025)

Prebiotic Peptide Synthesis: How Did Longest Peptide Appear? - Yuling Yang; Zhibiao Wang; Jin Bai; Hai Qiao (Journal of Molecular Evolution, 2025)

The tomato gene Ty-6, encoding DNA polymerase delta subunit 1, confers broad resistance to Geminiviruses - Xuexue Shen; Upinder Gill; Marjon Arens; Zhe Yan; Yuling Bai; Samuel F. Hutton; Anne-Marie A. Wolters (Theoretical and Applied Genetics, 2025)
Key message The tomato Ty-6 gene conferring resistance against begomoviruses has been cloned and shown to be a variant of DNA polymerase delta subunit 1. Abstract Ty-6 is a major resistance gene of tomato that provides resistance against monopartite and bipartite begomoviruses. The locus was previously mapped on chromosome 10, and in this study, we fine-mapped Ty-6 to a region of 47 kb, including four annotated candidate genes. Via whole-genome resequencing of Ty-6 breeding lines and several susceptible breeding lines, the polymorphisms in gene sequences were discovered and gene-associated markers were developed for marker-assistant breeding. Further, virus-induced gene silencing and candidate gene overexpressing in susceptible tomatoes revealed that Ty-6- mediated resistance is controlled by Solyc10g081250, encoding the DNA polymerase delta subunit 1, SlPOLD1 . The single nucleotide polymorphism of Ty-6 results in an amino acid change that might influence the fidelity of virus DNA replication.

Activity of anaerobic methane oxidation driven by different electron acceptors and the relative microbiome in paddy fields across various rice growth periods and soil layers - Yuling Yang; Lidong Shen; Caiyu Geng; Bingjie Ren; Yanan Bai; Jinghao Jin; Wangting Yang (Biology and Fertility of Soils, 2024)

Active role of iron-dependent AOM in paddy fields under different long-term fertilizer management schemes - Yuling Yang; Lidong Shen; Yuhan Jin; Yanan Bai; Shuwei Wang; Xu Zhao (Science of The Total Environment, 2024)

The impact of population change on social-ecological systems’ vulnerability: A case of the Qinling-Daba Mountains of Southern Shaanxi in China - Runyang Li; Jia Chen; Xinjun Yang; Sha Yin; Ruohan Shi; Yuling Bai; Li Xu (Journal of Cleaner Production, 2024)

The interplay of soil physicochemical properties, methanogenic diversity, and abundance governs methane production potential in paddy soil subjected to multi-decadal straw incorporation - Yuling Yang; Lidong Shen; Evgenios Agathokleous; Shuwei Wang; Yuhan Jin; Yanan Bai; Wangting Yang; Bingjie Ren; Jinghao Jin; Xu Zhao (Environmental Research, 2024)

Heterogeneous variations in wintertime PM2.5 sources, compositions and exposure risks at urban/suburban rural/remote rural areas in the post COVID-19/Clean-Heating period - Zhiyong Li; Zhuangzhuang Ren; Chen Liu; Zhi Ning; Jixiang Liu; Jinming Liu; Zhen Zhai; Xiaohua Ma; Lan Chen; Yuling Zhang; Longkai Bai; Shaofei Kong (Atmospheric Environment, 2024)

Vertical and temporal variations in activity, abundance, and composition of nitrite-driven anaerobic methanotrophs in a paddy field - Caiyu Geng; Lidong Shen; Bingjie Ren; Hechen Huang; Jinghao Jin; Wangting Yang; Evgenios Agathokleous; Jiaqi Liu; Yuling Yang; Yanan Bai; Yuzhi Song (Applied Soil Ecology, 2024)

Variations of activity and community structure of nitrite-driven anaerobic methanotrophs in soils between native and invasive species in China's coastal wetlands - Jiaqi Liu; Weiqi Wang; Lidong Shen; Yanan Bai; Wangting Yang; Yuling Yang; Jiangbing Xu; Maohui Tian; Xin Liu; Jinghao Jin; Yuzhi Song (European Journal of Soil Biology, 2024)

Equal importance of humic acids and nitrate in driving anaerobic oxidation of methane in paddy soils - Yanan Bai; Yanping Wang; Lidong Shen; Bo Shang; Yang Ji; Bingjie Ren; Wangting Yang; Yuling Yang; Zhiguo Ma; Zhaozhong Feng (Science of The Total Environment, 2024)

Establishment of evaluation system for biological remediation on organic pollution in groundwater using slow-release agents - Xinyue Du; Xiaoran Zhang; Junfeng Liu; Ziyang Zhang; Liyuan Wu; Xiaojuan Bai; Chaohong Tan; Yongwei Gong; Yuling Zhang; Haiyan Li (Science of The Total Environment, 2023)

Co-application of biochar and organic amendments on soil greenhouse gas emissions: A meta-analysis - Jia Fu; Xuhui Zhou; Yanghui He; Ruiqiang Liu; Yixian Yao; Guiyao Zhou; Hongyang Chen; Lingyan Zhou; Yuling Fu; Shahla Hosseini Bai (Science of The Total Environment, 2023)

Horizontal and vertical distribution of nitrate-driven anaerobic methane oxidation process in coastal wetlands under different plant species cover across southeast China - Wangting Yang; Weiqi Wang; Lidong Shen; Yanan Bai; Jiaqi Liu; Yuling Yang; Hechen Huang; Bingjie Ren (CATENA, 2023)

Insights into electrogenerated intermediates and rapid screening of electrochemical reactions by surface-modified carbon fiber paper redox spray ionization mass spectrometry - Jiahui Bai; Mingmai Bao; Shanshan Wang; Tianlun Wen; Yuling Li; Jing Zhang; Tiansheng Mei; Yinlong Guo (Analytica Chimica Acta, 2023)

Coconut shell biochar application in liquid-solid microextraction of triazine herbicides from multi-media environmental samples - Mengge Ma; Zongliang Niu; Zhuhua Tang; Jinyang Bai; Bei Li; Yuling Zhou; Yingying Wen (Analytica Chimica Acta, 2023)

Effects of abrupt and gradual increase of atmospheric CO2 concentration on methanotrophs in paddy fields - Lidong Shen; Bingjie Ren; Yuhan Jin; Xin Liu; Jinghao Jin; Hechen Huang; Maohui Tian; Wangting Yang; Yuling Yang; Jiaqi Liu; Caiyu Geng; Yanan Bai; et al. (Environmental Research, 2023)

Corrigendum to “Novel diketopyrrolopyrrole NIR-II fluorophores and DDR inhibitors for in vivo Chemo-photodynamic therapy of Osteosarcoma” [Chem. Eng. J. 446 (2022) 136929] - Xiaoding Cheng; Chong Zhang; Kun Shen; Huifan Liu; Caihong Bai; Qihang Ding; Mengting Guan; Junzhu Wu; Zhiquan Tian; Deliang Chen; Lin Cai; Xuechuan Hong; et al. (Chemical Engineering Journal, 2023)

Response of potential activity, abundance and community composition of nitrite‐dependent anaerobic methanotrophs to long‐term fertilization in paddy soils - Yuling Yang; Lidong Shen; Yanan Bai; Xu Zhao; Shuwei Wang; Jiaqi Liu; Xin Liu; Maohui Tian; Wangting Yang; Jinghao Jin; Hechen Huang; Hongsheng Wu (Environmental Microbiology, 2022)
The process of nitrite‐dependent anaerobic methane oxidation (n‐damo) catalysed by Candidatus Methylomirabilis oxyfera ( M . oxyfera )‐like bacteria is a novel pathway in regulating methane (CH 4 ) emissions from paddy fields. Nitrogen fertilization is essential to improve rice yields and soil fertility; however, its effect on the n‐damo process is largely unknown. Here, the potential n‐damo activity, abundance and community composition of M . oxyfera ‐like bacteria were investigated in paddy fields under three long‐term (32 years) fertilization treatments, i.e. unfertilized control (CK), chemical fertilization (NPK) and straw incorporation with chemical fertilization (SNPK). Relative to the CK, both NPK and SNPK treatments significantly ( p M . oxyfera ‐like bacteria. The variation of soil organic carbon (OrgC) content and inorganic nitrogen content caused by the input of chemical fertilizers and straw returning were identified as the key factors affecting the potential n‐damo activity and the abundance of M . oxyfera ‐like bacteria. However, the community composition and diversity of M . oxyfera ‐like bacteria did not change significantly by the input of fertilizers. Overall, our results provide the first evidence that long‐term fertilization greatly stimulates the n‐damo process, indicating its active role in controlling CH 4 emissions from paddy fields.

A new challenge in melon resistance breeding: the ToLCNDV case - Lampros Siskos; Lei Cui; Chen Wang; Richard G. F. Visser; Yuling Bai; Henk J. Schouten (Euphytica, 2022)
Tomato leaf curl New Dehli virus (ToLCNDV) is a whitefly transmitted plant virus that is affecting European melon cultivation for over a decade. Since its first introduction in the Mediterranean basin the virus has been associated with significant economic losses including lower yields and cracked non-marketable fruits in Spain and other key cucurbits production areas. Since there is no chemical application against viral pathogens the focus is geared towards resistance breeding. Various QTLs associated with ToLCNDV resistance have been reported over the recent years in melon and other cucurbits. In the current review we summarize the latest advances in melon breeding for ToLCNDV resistance and present all relevant loci known so far in cucurbits. As a way forward in the future we propose an alternative to traditional resistance gene introgression breeding by exploiting the knowledge on genes that confer susceptibility to the virus in melon and other cucurbits.

Analysis of allelic variants of RhMLO genes in rose and functional studies on susceptibility to powdery mildew related to clade V homologs - Peihong Fang; Paul Arens; Xintong Liu; Xin Zhang; Deepika Lakwani; Fabrice Foucher; Jérémy Clotault; Juliane Geike; Helgard Kaufmann; Thomas Debener; Yuling Bai; Zhao Zhang; et al. (Theoretical and Applied Genetics, 2021)
Key message Rose has 19 MLO genes. Of these, RhMLO1 and RhMLO2 were shown to be required for powdery mildew infection, which suggests their potential as susceptibility targets towards disease resistance. Abstract Powdery mildew, caused by Podosphaera pannosa , is one of the most serious and widespread fungal diseases for roses, especially in greenhouse-grown cut roses. It has been shown that certain MLO genes are involved in powdery mildew susceptibility and that loss of function in these genes in various crops leads to broad-spectrum, long-lasting resistance against this fungal disease. For this reason, these MLO genes are called susceptibility genes. We carried out a genome-wide identification of the MLO gene family in the Rosa chinensis genome, and screened for allelic variants among 22 accessions from seven different Rosa species using re-sequencing and transcriptome data. We identified 19 MLO genes in rose, of which four are candidate genes for functional homologs in clade V, which is the clade containing all dicot MLO susceptibility genes. We detected a total of 198 different allelic variants in the set of Rosa species and accessions, corresponding to 5–15 different alleles for each of the genes. Some diploid Rosa species shared alleles with tetraploid rose cultivars, consistent with the notion that diploid species have contributed to the formation of tetraploid roses. Among the four RhMLO genes in clade V, we demonstrated using expression study, virus-induced gene silencing as well as transient RNAi silencing that two of them, RhMLO1 and RhMLO2 , are required for infection by P. pannosa and suggest their potential as susceptibility targets for powdery mildew resistance breeding in rose.

Genetic Architecture of Childhood Kidney and Urological Diseases in China - Ye Fang; Hua Shi; Tianchao Xiang; Jiaojiao Liu; Jialu Liu; Xiaoshan Tang; Xiaoyan Fang; Jing Chen; Yihui Zhai; Qian Shen; Guomin Li; Li Sun; et al. (Phenomics, 2021)
Kidney disease is manifested in a wide variety of phenotypes, many of which have an important hereditary component. To delineate the genotypic and phenotypic spectrum of pediatric nephropathy, a multicenter registration system is being implemented based on the Chinese Children Genetic Kidney Disease Database (CCGKDD). In this study, all the patients with kidney and urological diseases were recruited from 2014 to 2020. Genetic analysis was conducted using exome sequencing for families with multiple affected individuals with nephropathy or clinical suspicion of a genetic kidney disease owing to early-onset or extrarenal features. The genetic diagnosis was confirmed in 883 of 2256 (39.1%) patients from 23 provinces in China. Phenotypic profiles showed that the primary diagnosis included steroid-resistant nephrotic syndrome (SRNS, 23.5%), glomerulonephritis (GN, 32.2%), congenital anomalies of the kidney and urinary tract (CAKUT, 21.2%), cystic renal disease (3.9%), renal calcinosis/stone (3.6%), tubulopathy (9.7%), and chronic kidney disease of unknown etiology (CKDu, 5.8%). The pathogenic variants of 105 monogenetic disorders were identified. Ten distinct genomic disorders were identified as pathogenic copy number variants (CNVs) in 11 patients. The diagnostic yield differed by subgroups, and was highest in those with cystic renal disease (66.3%), followed by tubulopathy (58.4%), GN (57.7%), CKDu (43.5%), SRNS (29.2%), renal calcinosis /stone (29.3%) and CAKUT (8.6%). Reverse phenotyping permitted correct identification in 40 cases with clinical reassessment and unexpected genetic conditions. We present the results of the largest cohort of children with kidney disease in China where diagnostic exome sequencing was performed. Our data demonstrate the utility of family-based exome sequencing, and indicate that the combined analysis of genotype and phenotype based on the national patient registry is pivotal to the genetic diagnosis of kidney disease.

Comparative genomics reveals the in planta‐ secreted Verticillium dahliae Av2 effector protein recognized in tomato plants that carry the V2 resistance locus - Edgar A. Chavarro‐Carrero; Jasper P. Vermeulen; David E. Torres; Toshiyuki Usami; Henk J. Schouten; Yuling Bai; Michael F. Seidl; Bart P. H. J. Thomma (Environmental Microbiology, 2021)
Summary Plant pathogens secrete effector molecules during host invasion to promote colonization. However, some of these effectors become recognized by host receptors to mount a defence response and establish immunity . Recently, a novel resistance was identified in wild tomato, mediated by the single dominant V2 locus, to control strains of the soil‐borne vascular wilt fungus Verticillium dahliae that belong to race 2 . With comparative genomics of race 2 strains and resistance‐breaking race 3 strains, we identified the avirulence effector that activates V2 resistance, termed Av2 . We identified 277 kb of race 2‐specific sequence comprising only two genes encoding predicted secreted proteins that are expressed during tomato colonization. Subsequent functional analysis based on genetic complementation into race 3 isolates and targeted deletion from the race 1 isolate JR2 and race 2 isolate TO22 confirmed that one of the two candidates encodes the avirulence effector Av2 that is recognized in V2 tomato plants. Two Av2 allelic variants were identified that encode Av2 variants that differ by a single acid. Thus far, a role in virulence could not be demonstrated for either of the two variants.

On the origin and dispersal of cultivated spinach (Spinacia oleracea L.) - Arnau Ribera; Rob van Treuren; Chris Kik; Yuling Bai; Anne-Marie A. Wolters (Genetic Resources and Crop Evolution, 2021)
Spinach ( Spinacia oleracea L.) is an economically important crop that is cultivated and consumed worldwide. Spinach is interfertile with the wild species S. tetrandra Steven ex M. Bieb. and S. turkestanica Iljin that therefore are presumed to include the most likely crop ancestor. Here we studied variation in 60 Single Nucleotide Polymorphisms (SNP) previously identified in S. oleracea to address the issue of crop ancestry and domestication region. For this purpose we investigated 95 accessions, including 54 spinach landraces from a wide geographic area in Europe and Asia and 16 S. tetrandra and 25 S. turkestanica populations of which the majority had only recently become available. Compared to S. tetrandra substantially higher levels of amplification success and higher levels of variation were detected for S. turkestanica , indicating that S. oleracea is genetically closer to S. turkestanica than to S. tetrandra . Our phylogenetic and population structure analysis supported the conclusion that S. turkestanica is the most likely ancestor of cultivated spinach. In addition, these analyses revealed a group of S. oleracea landraces from Eastern and Southern Asia with a strong genetic resemblance to S. turkestanica . This group includes landraces from Afghanistan and Pakistan, which are part of the native distribution range of S. turkestanica . The domestication of spinach may therefore have occurred more eastwards than generally assumed. Furthermore, our study provides support for the hypothesis that after domestication, spinach was introduced into China via Nepal. Additional collecting of spinach landraces is recommended in order to allow the more precise reconstruction of the crop migration routes.

An interactive motion-tracking system for home-based assessing and training reach-to-target tasks in stroke survivors—a preliminary study - Wenke Fan; Yuling Zhang; Qing Mei Wang; Yulong Bai; Yi Wu (Medical & Biological Engineering & Computing, 2020)

A review on the genetic resources, domestication and breeding history of spinach (Spinacia oleracea L.) - Arnau Ribera; Yuling Bai; Anne-Marie A. Wolters; Rob van Treuren; Chris Kik (Euphytica, 2020)
This paper addresses the genetic resources, domestication and breeding history of spinach as a comprehensive review of these crop aspects is currently unavailable. It is shown that the availability of genetic resources of wild relatives belonging to the primary gene pool is currently very limited, which hampers breeding and research activities. Therefore, new collecting expeditions are clearly warranted. The domestication of spinach is discussed on the basis of its presumed migration routes and the traits that were probably involved in the domestication syndrome. Spinach is thought to have domesticated in former Persia. Migration then occurred eastwards to China and westwards to Europe, but additional genetic data are needed to reveal the most likely migration routes. Morphological changes in pistillate flowers and loss of dormancy are identified as the main traits involved in the domestication syndrome of spinach. To a large extent we could re-construct the relationships between spinach cultivars that were developed until the 1950s, but this appeared difficult for the more recent cultivars due to intellectual property protection by breeding companies. Resistance against downy mildew has been the main breeding target in spinach. The introgression of NBS-LRR resistance genes from wild relatives is the major strategy to develop downy mildew resistant cultivars. However, the use of loss-of-function alleles of susceptibility genes may provide a more durable strategy to develop resistant cultivars. So far, abiotic resistance and quality traits have received minor attention in spinach research and breeding. This is expected to change considering the potential effects of climate change on these traits.

Differential magnitude of rhizosphere effects on soil aggregation at three stages of subtropical secondary forest successions - Ruiqiang Liu; Xuhui Zhou; Jiawei Wang; Junjiong Shao; Yuling Fu; Chao Liang; Enrong Yan; Xiaoyong Chen; Xihua Wang; Shahla Hosseini Bai (Plant and Soil, 2019)

Trichomes: interaction sites of tomato leaves with biotrophic powdery mildew pathogens - Tomoko Suzuki; Tomoe Murakami; Yoshihiro Takizumi; Hiroyuki Ishimaru; Daiki Kudo; Yoshihiro Takikawa; Yoshinori Matsuda; Koji Kakutani; Yuling Bai; Teruo Nonomura (European Journal of Plant Pathology, 2018)

Functional characterization of the powdery mildew susceptibility gene SmMLO1 in eggplant (Solanum melongena L.) - Valentina Bracuto; Michela Appiano; Luigi Ricciardi; Deniz Göl; Richard G. F. Visser; Yuling Bai; Stefano Pavan (Transgenic Research, 2017)

Silencing of six susceptibility genes results in potato late blight resistance - Kaile Sun; Anne-Marie A. Wolters; Jack H. Vossen; Maarten E. Rouwet; Annelies E. H. M. Loonen; Evert Jacobsen; Richard G. F. Visser; Yuling Bai (Transgenic Research, 2016)

Down-regulation of Arabidopsis DND1 orthologs in potato and tomato leads to broad-spectrum resistance to late blight and powdery mildew - Kaile Sun; Anne-Marie A. Wolters; Annelies E. H. M. Loonen; Robin P. Huibers; René van der Vlugt; Aska Goverse; Evert Jacobsen; Richard G. F. Visser; Yuling Bai (Transgenic Research, 2016)

Detection of an inversion in the Ty-2 region between S. lycopersicum and S. habrochaites by a combination of de novo genome assembly and BAC cloning - Anne-Marie A. Wolters; Myluska Caro; Shufang Dong; Richard Finkers; Jianchang Gao; Richard G. F. Visser; Xiaoxuan Wang; Yongchen Du; Yuling Bai (Theoretical and Applied Genetics, 2015)

Identification of candidate MLO powdery mildew susceptibility genes in cultivated Solanaceae and functional characterization of tobacco NtMLO1 - Michela Appiano; Stefano Pavan; Domenico Catalano; Zheng Zheng; Valentina Bracuto; Concetta Lotti; Richard G. F. Visser; Luigi Ricciardi; Yuling Bai (Transgenic Research, 2015)

Combined biotic and abiotic stress resistance in tomato - Christos Kissoudis; Rawnaq Chowdhury; Sjaak van Heusden; Clemens van de Wiel; Richard Finkers; Richard G. F. Visser; Yuling Bai; Gerard van der Linden (Euphytica, 2015)
Abiotic and biotic stress factors are the major constrains for the realization of crop yield potential. As climate change progresses, the spread and intensity of abiotic as well as biotic stressors is expected to increase, with increased probability of crops being exposed to both types of stress. Shielding crops from combinatorial stress requires a better understanding of the plant’s response and its genetic architecture. In this study, we evaluated resistance to salt stress, powdery mildew and to both stresses combined in tomato, using the Solanum habrochaites LYC4 introgression line (IL) population. The IL population segregated for both salt stress tolerance and powdery mildew resistance. Using SNP array marker data, QTLs were identified for salt tolerance as well as Na + and Cl − accumulation. Salt stress increased the susceptibility of the population to powdery mildew in an additive manner. Phenotypic variation for disease resistance was reduced under combined stress as indicated by the coefficient of variation. No correlation was found between disease resistance and Na + and Cl − accumulation under combined stress Most genetic loci were specific for either salt stress tolerance or powdery mildew resistance. These findings increase our understanding of the genetic regulation of responses to abiotic and biotic stress combinations and can provide leads to more efficiently breeding tomatoes and other crops with a high level of disease resistance while maintaining their performance in combination with abiotic stress.

Activation tagging of ATHB13 in Arabidopsis thaliana confers broad-spectrum disease resistance - Dongli Gao; Michela Appiano; Robin P. Huibers; Xi Chen; Annelies E. H. M. Loonen; Richard G. F. Visser; Anne -Marie A. Wolters; Yuling Bai (Plant Molecular Biology, 2014)

Identification of candidate genes required for susceptibility to powdery or downy mildew in cucumber - Henk J. Schouten; Julian Krauskopf; Richard G. F. Visser; Yuling Bai (Euphytica, 2014)
Powdery mildew (PM, caused by Podosphaera fusca ) and downy mildew (DM, caused by Pseudoperonospora cubensis ) are important diseases of cucumber ( Cucumis sativus ). Breeding for resistance has been undertaken since the 1940s, but underlying resistance genes have not been functionally analysed yet. The published genome sequence of cucumber catalyses the search for such genes. Genetic studies have indicated that resistances to PM and DM in cucumber are often inherited recessively, which indicates the presence of susceptibility genes (S-genes). Therefore we analyzed the cucumber genome for homologs of functionally proven S-genes known from other plant species. We identified 13 MLO -like genes in cucumber, three of which cluster in Clade V, the clade that contains all known MLO -like susceptibility genes to powdery mildews in other dicots. The expression of one of these three genes, CsaMLO1, located on chromosome 1, was upregulated after PM inoculation. It co-localizes with a QTL for PM resistance previously identified. Also homologs of the susceptibility genes PMR4 and PMR5 are located at this QTL. The second MLO -like gene from Clade V ( CsaMLO8 ) resides in a recessively inherited major QTL for PM resistance at the bottom of chromosome 5, together with a PMR6 -like gene. Two major QTL for DM recessive resistance at the top of chromosome 5 co-localize with CsaDMR6 - 2 , which is homologous to the DMR6 susceptibility gene in Arabidopsis . This study has identified several candidate genes for susceptibility to PM and DM in cucumber that may explain QTL for recessively inherited resistance, reported earlier.

The Ph-3 gene from Solanum pimpinellifolium encodes CC-NBS-LRR protein conferring resistance to Phytophthora infestans - Chunzhi Zhang; Lei Liu; Xiaoxuan Wang; Jack Vossen; Guangcun Li; Tao Li; Zheng Zheng; Jianchang Gao; Yanmei Guo; Richard G. F. Visser; Junming Li; Yuling Bai; et al. (Theoretical and Applied Genetics, 2014)

Genetics and molecular mechanisms of resistance to powdery mildews in tomato (Solanum lycopersicum) and its wild relatives - Alireza Seifi; Dongli Gao; Zheng Zheng; Stefano Pavan; Luigi Faino; Richard G. F. Visser; Anne-Marie A. Wolters; Yuling Bai (European Journal of Plant Pathology, 2014)

Fine mapping of the Ph-3 gene conferring resistance to late blight (Phytophthora infestans) in tomato - Chunzhi Zhang; Lei Liu; Zheng Zheng; Yuyan Sun; Longxi Zhou; Yuhong Yang; Feng Cheng; Zhonghua Zhang; Xiaowu Wang; Sanwen Huang; Bingyan Xie; Yongchen Du; et al. (Theoretical and Applied Genetics, 2013)

Genetic mapping of gummy stem blight (Didymella bryoniae) resistance genes in Cucumis sativus-hystrix introgression lines - Lina Lou; Hongying Wang; Chuntao Qian; Jia Liu; Yuling Bai; Jinfeng Chen (Euphytica, 2013)

How to effectively deploy plant resistances to pests and pathogens in crop breeding - A. Seifi; R. G. F. Visser; Yuling Bai (Euphytica, 2013)

Fine mapping of two major QTLs conferring resistance to powdery mildew in tomato - Luigi Faino; Shiva Azizinia; Benyamin Houshyani Hassanzadeh; Estelle Verzaux; Maria Raffaella Ercolano; Richard G. F. Visser; Yuling Bai (Euphytica, 2012)

Pea powdery mildew er1 resistance is associated to loss-of-function mutations at a MLO homologous locus - Stefano Pavan; Adalgisa Schiavulli; Michela Appiano; Angelo R. Marcotrigiano; Fabrizio Cillo; Richard G. F. Visser; Yuling Bai; Concetta Lotti; Luigi Ricciardi (Theoretical and Applied Genetics, 2011)

Identification and mapping of quantitative resistance to late blight (Phytophthora infestans) in Solanum habrochaites LA1777 - Junming Li; Lei Liu; Yuling Bai; Richard Finkers; Feng Wang; Yongchen Du; Yuhong Yang; Bingyan Xie; Richard G. F. Visser; Adriaan W. van Heusden (Euphytica, 2011)

Seedling salt tolerance in tomato - Junming Li; Lei Liu; Yuling Bai; Pujuan Zhang; Richard Finkers; Yongchen Du; Richard G. F. Visser; Adriaan W. van Heusden (Euphytica, 2011)

Map- vs. homology-based cloning for the recessive gene ol-2 conferring resistance to tomato powdery mildew - Stefano Pavan; Zheng Zheng; Mariya Borisova; Petra van den Berg; Concetta Lotti; Claudio De Giovanni; Pim Lindhout; Hans de Jong; Luigi Ricciardi; Richard G. F. Visser; Yuling Bai (Euphytica, 2008)

Quantitative resistance to Botrytis cinerea from Solanum neorickii - Richard Finkers; Yuling Bai; Petra van den Berg; Ralph van Berloo; Fien Meijer-Dekens; Arjen ten Have; Jan van Kan; Pim Lindhout; Adriaan W. van Heusden (Euphytica, 2008)

Distinct reorganization of the genome transcription associates with organogenesis of somatic embryo, shoots, and roots in rice - Ning Su; Kun He; Yuling Jiao; Chen Chen; Junli Zhou; Lei Li; Sulan Bai; Xueyong Li; Xing Wang Deng (Plant Molecular Biology, 2007)

Tomato defense to the powdery mildew fungus: differences in expression of genes in susceptible, monogenic- and polygenic resistance responses are mainly in timing - Chengwei Li; Yuling Bai; Evert Jacobsen; Richard Visser; Pim Lindhout; Guusje Bonnema (Plant Molecular Biology, 2006)